Understanding politics : ideas, institutions, and issues - Magstadt, Thomas M.
"Politics is a gateway to a broader and better understanding of human nature, society and the world" is the inspiration behind Magstadt's UNDERSTANDING POLITICS: IDEAS, INSTITUTIONS, AND ISSUES. The 13th Edition challenges you with its analysis of three fundamental premises: Politics is a pervasive force in modern society; government is too important to be left in the hands of a few; and the right to participate in public life is a precious thing unique to republics. Timely and relevant, it provides in-depth coverage of contemporary political issues and places them in the context of more enduring underlying questions. It focuses on key topics like ideology, citizenship, voting behavior, leadership and foreign policy as well as emerging issues, including the Trump presidency, social media in politics, Brexit, China as partner and rival, and populism and nativism as a reaction to globalism." -- Amazon.